Empowerment of Elementary School Students through Physical Activity Gymnastics Program in Medan City - Arvin Suhendra; Yunita Yunita; Aries Dc Silaban; Arjuna Arjuna; Aqila Azura (Joska: Jurnal Isori Kampar, 2025)
Objectives: Physical inactivity among elementary school students has become a growing concern in urban areas, including Medan City. The lack of structured physical activity programs in schools contributes to declining fitness levels and increases the risk of childhood obesity. This community service program addresses the urgent need to promote physical activity through gymnastics exercises among elementary school students. This program aimed to empower elementary school students by implementing a structured gymnastics-based physical activity program, improving students' knowledge about the importance of physical fitness, and enhancing their motor skills through systematic exercise routines. Methods: The program was conducted at three elementary schools in Medan City, involving 150 students aged 9-12 years. The implementation included socialization sessions, gymnastics training workshops for teachers, practical demonstrations, and regular practice sessions over eight weeks. Pre-test and post-test assessments were conducted using fitness tests and questionnaires to evaluate knowledge improvement. Results: The results showed significant improvement in students' physical fitness levels (78% increase in cardiovascular endurance), knowledge about physical activity benefits (85% improvement), and motor skill proficiency (72% enhancement). Student satisfaction reached 92%, and teacher competency in delivering gymnastics instruction increased by 88%. Conclusion: This program successfully established sustainable physical activity routines in partner schools, trained 15 teachers as gymnastics instructors, and created a replicable model for other schools in Medan City.